The Effectiveness of Peer Tutoring Learning Model Assisted by Canva-Based Learning Media on Mathematical Understanding and Learning Interest of Student at SMPN 14 Cilegon - Handayani, Astuti; Hamidah, Hamidah; Caesarani, Sarah; Kusuma, Jaka Wijaya (Nindikayla Institute, 2025)
This study aims to determine the effectiveness of the peer tutoring learning model assisted by Canva-based learning media on students' mathematical understanding and learning interest. The background of this study is based on the low mathematical understanding and learning interest of students at SMPN 14 Cilegon in mathematics learning, as well as the lack of variety of learning media used. This study uses a quantitative method with a quasi-experimental design of the nonequivalent pretest-posttest control group design. The subjects of the study were grade VII students of SMPN 14 Cilegon, with class VII C as the experimental class and class VII A as the control class. The research instruments included a mathematical understanding test and a student learning interest questionnaire. The results of the data analysis showed that, 1) the increase in mathematical understanding of students who were given learning with the peer tutoring model assisted by Canva-based learning media was better than those who used conventional learning, 2) the learning interest of students who were given learning with the peer tutoring model assisted by Canva-based learning media was better than those who used conventional learning. From the results of the N-Gain data analysis of the experimental and control classes, a sig. value was obtained. (2-tailed) 0.000 <0.05 and for the average learning interest of the questionnaire 83.07 high category in the experimental class, while in the control class obtained an average questionnaire of 71.67. So it can be concluded that there is an increase in mathematical understanding and learning interest of students who use peer tutor learning model assisted by Canva-based learning media better than students who use conventional learning. Thus, the peer tutor learning model assisted by Canva media is effective in improving mathematical understanding and learning interest of students of SMPN 14 Cilegon